Anatomical variations and clinical relevance of dorsal sacral foramina in North Indians - Khanna, Jugesh; Chauhan, Renu (International Journal of Research in Medical Sciences, 2017)
Lateral side of each intermediate crest has four dorsal sacral foramina for the passage of posterior division of the sacral nerves. Not only they serve as an important landmark in placement of spinal instrumentation but are also of great importance in transsacral block of sacral nerves for producing analgesia and anesthesia in pelvic surgeries. Therefore a study on the variation in number of dorsal sacral foramina was conducted in 60 adult dry North Indian sacra. Three dorsal sacral foramina were seen on the lateral side of each intermediate crest in four sacra (6.6%) and five in 6 sacra (10%) amongst all the sacra examined. Either a single pair, double pair or totally absent foramina were not observed in any of the sacra seen. This study revealed that there is variation in the number of dorsal sacral foramina. Anaesthetists should be aware of this disparity to be able to perform trans-sacral nerve block successfully. Radiologists must also know about this variation to interpret the radiographs of lumbosacral region. Neurologist and orthopedist should also be cognizant of this fact to diagnose patients presenting with bizarre clinical findings.